Assessing STEM competences and needs alignment in pre-service chemistry teachers - Slemy, Salim A. S.; Hussien, Suhailah; Dawood Abdulmalek Yahya Al-Hidabi, Dawood; Said, Sadri. A. (SUMAIT University, 2025)
This study assessed the competence level in the STEM approach among university chemistry preservice teachers. It employs a mixed-methods approach, integrating both quantitative and qualitative data collection. The questionnaire was administered to 218 pre-service teachers, a focus group discussion was conducted with 140 pre-service teachers in a group of 10 and interviews were conducted with 10 STEM field experts. The quantitative findings demonstrate the limited level of competence in the STEM approach among 2018 pre-service teachers. Statistically, there is no significant correlation between STEM competence levels and variables such as gender, specialization, or educational level because of generally low STEM literacy among pre-service teachers. The actual levels of STEM competencies of pre-service teachers in term of knowledge, skills and attitude do not align with their needs and expectations. The pre-service teachers’ needs and expectations are higher than their competencies, suggesting the importance of designing STEM framework to enhance STEM competence and achieve the expected needs. The qualitative findings revealed similar findings of lower level of STEM Competences in term of STEM literacy, STEMPedagogical Content knowledge and STEM-Value. The study recommend designing and developing value-Based STEM Chemistry Framework and innovation focused STEM Module to cultivate innovation skills. The designing of STEM Professional Development Framework (STEM-PDF) is also recommended for innovative teaching methods to cultivate STEM-PCK, for enabling pre-service teachers to develop practical skills impacting STEM Competencies to their students.